A STUDY ON SERVICE QUALITY AND SATISFACTION OF TOURISTS TOWARDS RELIGIOUS TOUR OPERATORS IN CHENNAI CITY - Milton, T. (International Journal of Psychosocial Rehabilitation, 2020)
Quality of service is the most important aspect for tourists to make decision for their visits and travel plans and preference of tour operators among alternatives especially in religious tourism. The findings explicate that significant difference is there among service quality of religious tour operators and demographic profile of tourists. Reliability, responsiveness, empathy, assurance and tangibility are significantly and positively impacting satisfaction of tourists. Thus, religious tour operators should communicate preciously to tourists and they must give full confidence to tourists and they should improve their capabilities for giving services effectively to tourists. Besides, religious tour operators should have the best interest of tourists at heart and they must understand exact requirements of tourists. Furthermore, tour operators should provide services exactly as they assured and they must give services as required by tourists and they should ready to help tourists in all the times.